Leaf Vein Density of Tree Saplings Composing Lower Canopy in Tropical Forest Reflects Their Ecophysiological Characteristics - Yansen Yansen; Deselina Deselina (Universitas Gadjah Mada, 2020)
One factor affecting the survival of a species in a tropical ecosystem is its ability to respond to environmental conditions, which depend on their ecophysiological performances. Plants ability to transport water as a major environmental factor would determine their survival. The anatomy of xylem inside leaves and stem as water conductive tissue will dictate the rate of water transport through the plant stem and leaves. Leaf vein, which contains xylem vessels, dictates water transport through leaves and plant’s ability to control water loss through stomata. This research found that tree saplings composing a lower canopy of tropical forests have different ecophysiological attributes. Pioneer species, such as Cinnamomum sp., Diospyros macrophylla, Castanopsis costata, Elateriospermum tapos, and Ziziphus sp., have higher leaf vein density than primary species, such as a member of genus Garcinia, Shorea, Dipterocarpus, and Syzigium. It implies that pioneer species might have higher rates of water transport and consequently, higher rates of photosynthesis. If forest vegetation was more opened, then pioneer species may dominate the area as they are more tolerant of light. The Composition of forest vegetation with different ecophysiological characteristics may affect the forest dynamics and hydrological cycle.